GENDER AND SEASONAL FEATURES OF DEVELOPMENT PROCESS OF PHLEGMON OF MAXILLOFACIAL AREA - K. Vakulenko (Ukrainian Medical Stomatological Academy, 2015)
The article describes the patterns and characteristics of occurrence and course of phlegmon of the maxillofacial region, which are to determine the relationship of gender-seasonal characteristics. Increasing trend in recent years not only to increase the frequency and number of abscesses, but also to increase the number of complications. Complications, many authors attributed to changes in the nature of the disease and, often, it atypia. Noteworthy that most often the main contingent of patients phlegmons a person of working age, ie 20- 40 years of age, they occur most often complications. Therefore, it is advisable to treat cellulitis as one of the leading causes of temporary incapacity, disability and mortality in surgical dental patients. It should be noted, and poorly understood issue of gender characteristics and seasonal occurrence of abscesses maxillofacial area that we believe has its own laws it will study the possibility to specify tactics in a particular case. A retrospective study and analysis of case histories of 280 patients between 18 and 75 years who were treated at the clinic between 2006 and 2008 with a diagnosis of abscess of soft tissues of the maxillofacial area of a particular location. All patients - residents of the city of Kharkiv and Kharkiv region. Dominated by patients under the age of 40 years. Notes the prevalence of odontogenic causes of the inflammatory process in the autumn and winter, more often in men than in women. Noteworthy is the fact that, in general, the highest peak uptake in patients with soft tissue phlegmon of the maxillofacial area in the autumn and winter. Also of interest is a comparison of the treatment periods patients from the time of disease onset. Was more severe in males, it is connected not only with the later treatment, but also with a history of chronic diseases, alcohol and smoking. In the analysis of the available data may be noted that the most common source of infection at OOGP were mandibular second, first and third molars, premolars. Maxillary first and second molars, as well as the first molar. This confirms the opinion of other authors about the high prevalence of caries process, a low level of oral hygiene in the posterior teeth, and are not always effective endodontic root canal treatment. Less incidence of abscesses in women is associated with timely treatment to the dentist for treatment of dental diseases dental hard tissues and their complications. Also, in men, chronic inflammatory processes more severe than in women. Related somatic pathology complicates the course of cellulitis. Comparing the nature of the disease, patients' complaints, the clinical manifestations of the process may be noted that in men aged 20 to 40 years prevailed expressed complaints about the difficulty in opening the mouth, in men older than 60 - noted the current sluggish during the process. Appropriate manifestation process in women did not have statistically significant differences from the current process in men. Topographic analysis indicates that the predominant localization of the following - submandibular, submandibular and peripharyngeal. Noted that the abscesses and cellulitis observed in persons aged 20-30 years, which is associated with the greatest intensity of caries and difficult eruption of the lower wisdom tooth. The development and course of acute purulent inflammatory diseases of different areas of the head and neck depend on the concentration of the microflora, general, local non-specific and specific protective factors, the status of various organs and systems, as well as anatomical and topographical features of tissues. Frequent localization of abscesses in the submandibular region is a consequence of the prevalence of caries and its complications of posterior teeth of the lower jaw, this is also evidenced by the prevalence of odontogenic causes of the inflammatory process in the autumn-winter period, more common in men. You also can not ignore the fact that men inflammatory processes more severe than in women, which should also be considered in the development of prevention and organization of surgical dental care.